Extramedullary Osseointegration—A Novel Design of Percutaneous Osseointegration Prosthesis for Amputees - Sun, Yingying; Xu, Jinying; Lv, Shuang; Xu, Ziran; Li, Lisha; Li, Yan; Li, Yulin (Frontiers in Bioengineering and Biotechnology, 2022)
The percutaneous osseointegrated (OI) prostheses have greatly improved the overall quality of life for amputees. However, the long-term maintenance of the OI prostheses are still challenging. A major problem is bone resorption around the bone-implant-skin interface, which might cause implant loosening or osteomyelitis. Another problem is the breakage of connecting components between the intramedullary implant and external prosthesis due to excessive stress. We designed a novel osseointegration implant by changing the bone-implant contact from inner cortex to outer surface of cortical bone. In the current study, we compared the extramedullary cap-shaped implants with the intramedullary screw-type implants in rabbits. Osteointegration was confirmed at the interface of bone to implant contact (BIC) in both implant types. The external implant induced intramedullary bone regeneration in the medullary canal and increased the cortical bone density at the end of the stump. This study provides a new perspective on the design of osseointegration implants which might prevent the current reported complications of the intramedullary OI systems.